(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى معرفة مدى تأثير اضطراب النشاط الحركي على الأطفال، وهل له علاقة بتعرّض الطفل للحوادث (حوادث السير في دراستنا نموذجاً) إذا كان يعاني منه... أي أن يكون مستهدفاً للحوادث من خلال تعرضه لهذا الاضطراب. ومن ثمّ معاناته لاضطراب الضغوط التالية للصدمة (PTSD) نتيجة لصدمة الحوادث. نُفذّ البحث بالاعتماد على مقياس اضطراب فرط النشاط المصحوب بنقص الانتباه. من إعداد الزراد بعد القيام بدراسة استطلاعية للتأكد من صدق المقياس وثباته، كما تمّ الاعتماد على قائمة شطب الـ PTSD. إعداد عز. وتألفت عينة البحث من (10) طفل وطفلة في مرحلة التعليم الأساسي بمدينة دمشق. توصلت الدّراسة إلى عدد من النتائج يمكن تلخيصها بالنّقاط التاليّة: • تبيّن وجود علاقة ارتباطيّة بين اضطراب فرط النشاط وتعرّض الأطفال لحوادث سير. • تبيّن وجود علاقة ارتباطيّة بين اضطراب فرط النشاط وتعرّض الأطفال لاضطراب الضغوط التالية للصدمة. • تبيّن أن (29.72%) من الأطفال الذين تعرّضوا لحوادث سير يعانون اضطراب فرط النشاط الحركي, أي هم من الأطفال المستهدفين للحوادث. • تبيّن وجود فروق ذات دلالة إحصائية في اضطراب فرط النشاط الحركي بين الذكور والإناث وكانت الفروق لصالح الذكور. • تبيّن وجود فروق ذات دلالة إحصائية في أعراض فرط الحركة بين الذكور والإناث وكانت الفروق لصالح الذكور. • تبيّن عدم وجود فروق ذات دلالة إحصائية في أعراض نقص الانتباه بين الذكور والإناث. The research seeks determining the effect of disorder on the motor activity of children, and whether the child has to do with exposure to accidents (traffic accidents in our study model) when you have it. That is, the target of an accident by being subjected to this disorder, and, thus, suffering the disorder following traumatic stress (PTSD) as a result of traumatic accidents. The research is based on measurement PTSD by AL Zarrad after doing an exploratory study to ascertain the validity and reliability of the scale. It also relied on the pressure gauge disorder following traumatic stress by AZZ. The research sample consisted of (100) boys and girls in basic education that has been subjected to accidents in the city of Damascus. The study found a number of conclusions that can be summarized in the following points: • Ø show a correlation between hyperactivity disorder and vulnerability of children to traffic accidents. • Ø show a correlation between hyperactivity disorder and children’s exposure to the disruption of pressure following the shock. • Ø show that 29.72% of the children who were exposed to traffic accidents suffer from (ADHD), which they target children for accidents. • Ø show statistically significant differences in the (ADHD) among males and females and the differences are in favor of males • Ø show statistically significant differences in symptoms of hyperactivity among males and females and the differences are in favor of males. • Ø show the lack of statistically significant differences in symptoms of attention deficit between males and females. • Ø show statistically significant differences in symptoms impulsivity between males and females. Keywords: Post Traumatic Stress Disorder. Attention Deficit Hyperactivity Disorder